Evidence for interface-rate limited densification kinetics at Al2O3-GdAlO3 interfaces characterized by in situ ultrahigh temperature transmission electron microscopy. Issue 13 (October 2022) - Coffman, D. Keith; Ma, Yonghui; Barr, Christopher; Ouyang, Jia-Hu; Hattar, Khalid; Dillon, Shen J.
Abstract: The sintering behavior of single Al2 O3 particles resting on GdAlO3 is characterized using in situ transmission electron microscopy imaging. In bicrystal experiments, particles with lower Al2 O3 -GdAlO3 phase boundary energies shrink via Ostwald ripening with no evidence of densification that would result from an atomic flux along the interface. Particles with higher Al2 O3 -GdAlO3 phase boundary energies undergo intermittent rigid body motion associated with an interfacial flux mediated by interfacial line defects, e.g. disconnections. Long incubation periods elapse between these comparatively rapid rigid body motion events. The interfacial diffusivity during each event agrees with the magnitude of interfacial diffusion obtained from independent measurements of interfacial diffusivity. The results from the model experiments suggest that capillarity driven interfacial strain mediation, e.g. densification during sintering, is interface rate limited at the driving forces investigated.